Aramid diaphragm for lithium battery and preparation method of aramid diaphragm
By using aramid slurry combined with Tensil fibrillated slurry, titanium aluminum lithium nanoparticles and nanoceramic particles, the problem of holes and short circuits in traditional lithium-ion battery separators is solved, and the thermal stability and mechanical strength are achieved, and the safety and electrochemical performance of the battery are improved.
Patent Information
- Application Number
- CN202510198338.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-22
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-02-22
AI Technical Summary
Traditional lithium-ion battery separators are prone to shrink or melt at high temperatures, resulting in hole breakage, short circuit and battery safety problems.
Aramid slurry combined with aramid polymerization liquid, Tensil fibrillated slurry, titanium aluminum lithium nanoparticles and nanoceramic particles is coated on both sides of the base film to form an aramid coating to improve the heat resistance and mechanical strength of the membrane.
It significantly improves the thermal stability and mechanical strength of the lithium battery separator, reduces the heat shrinkage, and enhances the safety and electrochemical performance of the battery.
Smart Images

Figure BDA0005282223030000061 
Figure BDA0005282223030000071
Abstract
Description
Technical Field
[0001] The present application relates to the field of lithium battery separators, and in particular to an aramid separator for lithium batteries and a preparation method thereof. Background Art
[0002] As a core component of energy storage, lithium-ion batteries are widely used in consumer electronics, electric vehicles, grid energy storage and other fields. The diaphragm is a thin film with a microporous structure and is a key internal component with technical barriers in the lithium-ion battery industry chain. The main function of the diaphragm is to separate the positive and negative electrodes of the battery to prevent the two electrodes from contacting and short-circuiting. In addition, the micropores in the diaphragm also allow lithium ions to pass through to form a charge and discharge circuit.
[0003] Traditional diaphragm materials are mainly polyolefin porous membranes. However, due to the low melting point of polyolefin materials, when the battery temperature rises due to internal or external factors, the diaphragm will shrink or melt and then rupture, causing the positive and negative poles of the battery to come into contact, resulting in a short circuit in the battery, causing battery combustion and explosion and other accidents, seriously affecting the safety and stability of the battery. Summary of the invention
[0004] In order to improve the heat resistance and strength of traditional diaphragm materials, the present application provides an aramid diaphragm for a lithium battery and a preparation method thereof.
[0005] In the first aspect, the present application provides an aramid diaphragm for a lithium battery, which adopts the following technical solution: An aramid diaphragm for a lithium battery comprises an aramid slurry and a base film. The aramid slurry is coated on both sides of the base film to form an aramid coating. The aramid slurry comprises the following raw materials in parts by weight: 20-40 parts of aramid polymer solution, 5-10 parts of tencel fibrillated slurry, 1-3 parts of lithium titanium aluminum phosphate nanoparticles, 3-5 parts of nano-ceramic particles, and 8-15 parts of solvent; the aramid polymer solution comprises the following raw materials in parts by weight: 1-3 parts of p-phenylenediamine, 60-80 parts of polar solvent, 5-10 parts of terephthaloyl chloride, 1-3 parts of 3,4'-diaminodiphenyl ether, 1-3 parts of o-chloro-p-phenylenediamine, and 0.5-1 part of a polyether surfactant.
[0006] By adopting the above technical scheme, p-phenylenediamine, terephthaloyl chloride, 3,4'-diaminodiphenyl ether, and o-chloro-p-phenylenediamine are polycondensed to generate poly-p-phenylene terephthalamide, forming a para-aramid polymer solution, which has good solubility and can be directly used for lithium battery separator coating, so that the prepared aramid separator has good heat resistance and can reduce the thermal shrinkage of the lithium battery separator. An appropriate amount of polyether surfactant is added to the aramid polymer solution. The polyether surfactant combines with poly-p-phenylene terephthalamide on the one hand and dissolves in the solvent on the other hand, thereby promoting the polyether surfactant to be adsorbed on the interface between the aramid polymer solution and the solvent, reducing the interfacial tension, promoting the aramid slurry to have good fluidity and stability, facilitating subsequent coating and film formation, and is conducive to forming a uniform aramid coating. At the same time, the polyether surfactant can enhance the wettability of the aramid polymer solution and the aramid slurry, promoting the aramid slurry to be firmly bonded to the base film, and improving the structural stability and mechanical strength of the diaphragm.
[0007] Tencel fiber is processed by refining and fibrillation to form Tencel fibrillated pulp, which can form a porous three-dimensional network structure in the aramid slurry with aramid polymer solution, so that the aramid diaphragm has more pores, providing sufficient migration channels for lithium ions and improving the electrochemical performance of lithium batteries. Tencel fibrillated pulp can improve the flexibility and air permeability of aramid coating, thereby improving the electrochemical stability of lithium batteries.
[0008] Lithium titanium aluminum phosphate nanoparticles and nano-ceramic particles can improve the strength and thermal stability of the diaphragm. Lithium titanium aluminum phosphate nanoparticles can enhance the transmission capacity and cycle stability of lithium ions and improve the electrochemical stability of lithium batteries. Nano-ceramic particles have a higher melting point, which reduces the risk of short circuits between electrodes and diaphragms due to thermal contraction and improves battery safety.
[0009] Preferably, the polyether surfactant is one of polyethylene glycol, polypropylene oxide and polytetramethylene glycol.
[0010] Preferably, the solvent is a complex of a dispersing solvent and a co-solvent, the dispersing solvent is at least one of dimethylacetamide, dimethylformamide, dimethyl sulfoxide, and acetone, and the co-solvent is at least one of calcium chloride, lithium chloride, and potassium hydroxide.
[0011] Preferably, the Tencel fibrillated pulp is made by subjecting Tencel fibers as raw materials to pulping and fibrillation treatment, and the Tencel fibrillated pulp has a beating degree of 75-85° SR.
[0012] By adopting the above technical scheme, the beating degree of Tencel fibrillated slurry is controlled within the range of 75-85°SR, which increases the specific surface area of the fiber and the contact area between the Tencel fiber and the aramid polymer solution. At the same time, it can ensure that the Tencel fiber is evenly dispersed in the aramid slurry and maintains a good fiber structure, thereby improving the mechanical strength, structural stability and air permeability of the diaphragm.
[0013] Preferably, the nano-ceramic particles are silanized using a silane coupling agent, and the modification method comprises the following specific steps: mixing the nano-ceramic particles with the silane coupling agent and toluene, heating to 70-80° C. and stirring evenly, washing and drying to obtain silanized modified nano-ceramic particles.
[0014] By adopting the above technical solution and modifying the nano-ceramic particles with a silane coupling agent, the nano-ceramic particles can be evenly dispersed in the aramid slurry, the precipitation of ceramic particles can be reduced, and the strength of the aramid diaphragm can be evenly improved. At the same time, the addition of the silane coupling agent can further enhance the bonding force between the aramid slurry and the base film, and prolong the strength and structural stability of the aramid diaphragm.
[0015] Preferably, the nano-ceramic particles are at least one of nano-silicon dioxide, nano-titanium dioxide and nano-aluminum oxide.
[0016] Preferably, the aramid coating has a thickness of 3-8 μm, and the base film has a thickness of 5-20 μm.
[0017] In a second aspect, the present application provides a method for preparing an aramid diaphragm for a lithium battery, using the following technical solution: A method for preparing an aramid diaphragm for a lithium battery, comprising the following specific steps: The p-phenylenediamine, 3,4'-diaminodiphenyl and o-chloro-p-phenylenediamine are uniformly mixed, a polar solvent is added, and the mixture is stirred and dissolved at 10-30°C under the protection of nitrogen, and then the mixture is cooled to -5°C-0°C, terephthaloyl chloride and a polyether surfactant are added, and the mixture is stirred and reacted to obtain a reaction mixture, and the pH of the reaction mixture is adjusted to obtain an aramid polymerization solution; Aramid polymer solution, Tencel fibrillated pulp, lithium titanium aluminum phosphate nanoparticles, nano-ceramic particles and solvent are mixed, heated, stirred and dissolved to obtain aramid slurry, and then the aramid slurry is coated on both sides of the base film and dried to form an aramid coating to obtain an aramid diaphragm for lithium batteries.
[0018] By adopting the above technical solution, the prepared aramid membrane can have good thermal stability and strength, while maintaining good porosity and permeability, thereby improving the electrochemical performance of the lithium battery.
[0019] In summary, this application has the following beneficial effects: 1. Since the present application adds a polyether surfactant to the para-aramid slurry raw material, it can improve the wettability of the aramid slurry, enhance the bonding force between the aramid slurry and the base film, and form a uniform, heat-resistant aramid coating. The Tencel fibrillated slurry is combined with the aramid polymer to form an interconnected porous three-dimensional network structure in the aramid slurry system, thereby improving the pore structure of the aramid diaphragm and the electrochemical stability of the lithium battery. The use of lithium titanium aluminum phosphate nanoparticles and nano-ceramic particles improves the strength and thermal stability of the aramid diaphragm, reduces the risk of short circuits between the electrode and the diaphragm due to thermal contraction, and improves the safety of the battery.
[0020] 2. In this application, the Tencel fiber is subjected to a pulping and fibrillation treatment to form a Tencel fibrillated slurry, which increases the specific surface area of the fiber, increases the contact area between the Tencel fiber and the aramid polymer solution, and maintains a high fiber strength, thereby improving the mechanical strength, structural stability and air permeability of the aramid diaphragm. The nano-ceramic particles are silanized using a silane coupling agent to promote the uniform dispersion of the nano-ceramic particles in the aramid slurry, reduce the precipitation of ceramic particles, and improve the uniformity of the strength of the aramid diaphragm. DETAILED DESCRIPTION
[0021] The present application is further described in detail below with reference to the embodiments.
[0022] All raw materials in the examples are commercially available.
[0023] Preparation Example of Aramid Polymerization Solution Preparation Example 1 The aramid polymer solution includes the following raw materials in parts by weight: 2 kg of p-phenylenediamine, 70 kg of polar solvent, 8 kg of terephthaloyl chloride, 2 kg of 3,4'-diaminodiphenyl ether, 2 kg of o-chloro-p-phenylenediamine, and 0.8 kg of polyether surfactant, wherein the polar solvent is N-methylpyrrolidone and the polyether surfactant is polyethylene glycol 400.
[0024] The method for preparing aramid polymer solution comprises the following specific steps: Paraphenylenediamine, 3,4'-diaminodiphenyl and o-chloroparaphenylenediamine are uniformly mixed, a polar solvent is added, and the mixture is stirred and dissolved at 20°C under the protection of nitrogen, then the mixture is cooled to -3°C, terephthaloyl chloride and a polyether surfactant are added, and the mixture is stirred for reaction to obtain a reaction mixture, and a 15wt% sodium hydroxide aqueous solution is used to adjust the pH of the reaction mixture to neutral, and the aramid polymerization liquid is obtained after continuous filtration and degassing.
[0025] Preparation Example 2 The difference between Preparation Example 2 and Preparation Example 1 is that the amount of p-phenylenediamine used in the aramid polymer liquid raw material is 1 kg, the amount of polar solvent used is 60 kg, the amount of terephthaloyl chloride used is 5 kg, the amount of 3,4'-diaminodiphenyl ether used is 3 kg, the amount of o-chloro-p-phenylenediamine used is 3 kg, and the amount of polyether surfactant used is 0.5 kg.
[0026] Preparation Example 3 The difference between Preparation Example 3 and Preparation Example 1 is that the amount of p-phenylenediamine used in the aramid polymer liquid raw material is 3 kg, the amount of polar solvent used is 80 kg, the amount of terephthaloyl chloride used is 10 kg, the amount of 3,4'-diaminodiphenyl ether used is 1 kg, the amount of o-chloro-p-phenylenediamine used is 1 kg, and the amount of polyether surfactant used is 1 kg.
[0027] Preparation Example 4 The difference between Preparation Example 4 and Preparation Example 1 is that the polyether surfactant in the aramid polymerization liquid raw material is polypropylene oxide, and the molecular weight of polypropylene oxide is 5000.
[0028] Preparation Example 5 The difference between Preparation Example 5 and Preparation Example 1 is that no polyether surfactant is used in the aramid polymer liquid raw material.
[0029] The method for preparing aramid polymer solution comprises the following specific steps: The p-phenylenediamine, 3,4'-diaminodiphenyl and o-chloro-p-phenylenediamine are uniformly mixed, a polar solvent is added, and the mixture is stirred and dissolved at 20°C under the protection of nitrogen, then the mixture is cooled to -3°C, terephthaloyl chloride is added, and the mixture is stirred for reaction to obtain a reaction mixture, and a 15wt% sodium hydroxide aqueous solution is used to adjust the pH of the reaction mixture to neutral, and the aramid polymerization liquid is obtained after continuous filtration and degassing. Example
[0030] Example 1 This embodiment provides an aramid diaphragm for a lithium battery, including an aramid slurry and a base film. The aramid slurry is coated on both sides of the base film to form an aramid coating. The aramid slurry includes the following raw materials in parts by weight: 30 kg of aramid polymer solution, 8 kg of Tencel fibrillated slurry, 2 kg of lithium titanium aluminum phosphate nanoparticles, 4 kg of nano-ceramic particles, and 11 kg of solvent. The aramid polymer solution is derived from Preparation Example 1, the Tencel fibrillated slurry is made by using Tencel fiber as raw material for pulping and fibrillation treatment, the Tencel fibrillated slurry has a beating degree of 80°SR, and the lithium titanium aluminum phosphate nanoparticles are Li 1.3 Al 0.3 Ti 1.7 P3O 12The average particle size of lithium aluminum titanium phosphate nanoparticles is 80-100 nm, the nano-ceramic particles are nano-silicon dioxide, the average particle size of the nano-ceramic particles is 50-80 nm, the solvent is a complex of dimethylformamide and potassium chloride, and the mass ratio of dimethylformamide to potassium chloride is 1:0.5.
[0031] The method for preparing an aramid diaphragm for a lithium battery comprises the following specific steps: Aramid polymer liquid, Tencel fibrillated slurry, lithium titanium aluminum phosphate nanoparticles, nano-ceramic particles and solvent are mixed, stirred and dissolved to obtain aramid slurry, and then the aramid slurry is coated on both sides of the base film, the base film is a polypropylene diaphragm with a thickness of 15 μm and a porosity of 80%. The coating rate is 8 m / min, immersed in water for 10 s, and dried in a three-stage oven. The temperatures of each stage of the oven are 50°C, 60°C, and 65°C, respectively. The aramid coating with a thickness of 5 μm is formed by drying to obtain an aramid diaphragm for lithium batteries.
[0032] Example 2 The difference between Example 2 and Example 1 is that the amount of aramid polymer liquid used in the aramid slurry raw material is 20 kg, the amount of Tencel fibrillated slurry used is 10 kg, the amount of lithium titanium aluminum phosphate nanoparticles used is 1 kg, the amount of nano-ceramic particles used is 3 kg, and the amount of solvent used is 8 kg.
[0033] Example 3 The difference between Example 3 and Example 1 is that the amount of aramid polymer liquid used in the aramid slurry raw material is 40 kg, the amount of Tencel fibrillated slurry used is 5 kg, the amount of lithium titanium aluminum phosphate nanoparticles used is 3 kg, the amount of nano-ceramic particles used is 5 kg, and the amount of solvent used is 15 kg.
[0034] Example 4 The difference between Example 4 and Example 1 is that the aramid polymer solution in the aramid slurry raw material comes from Preparation Example 2.
[0035] Example 5 The difference between Example 5 and Example 1 is that the aramid polymer solution in the aramid slurry raw material comes from Preparation Example 3.
[0036] Example 6 The difference between Example 6 and Example 1 is that the aramid polymer solution in the aramid slurry raw material comes from Preparation Example 4.
[0037] Example 7 The difference between Example 7 and Example 1 is that the solvent in the aramid slurry raw material is a complex of dimethylacetamide and lithium chloride, and the mass ratio of dimethylacetamide to lithium chloride is 1:0.5.
[0038] Example 8 The difference between Example 8 and Example 1 is that the nano-ceramic particles in the aramid slurry raw material are silanized and modified using a silane coupling agent.
[0039] The method for preparing an aramid diaphragm for a lithium battery comprises the following specific steps: S1: Mix nano-ceramic particles with silane coupling agent KH-570 and toluene in a mass ratio of 1:0.5:1, heat to 75°C and stir for 2h, wash with ethanol and dry to obtain silanized modified nano-ceramic particles.
[0040] S2: Mix aramid polymer liquid, Tencel fibrillated slurry, lithium titanium aluminum phosphate nanoparticles, silanized modified nano-ceramic particles and solvent, stir and dissolve to obtain aramid slurry, and then apply the aramid slurry on both sides of the base film, the base film is a polypropylene diaphragm with a thickness of 15μm and a porosity of 80%. The coating rate is 8m / min, immersed in water for 10s, and dried in a three-stage oven. The temperatures of each stage of the oven are 50℃, 60℃, and 65℃ respectively. Dry to form an aramid coating with a thickness of 5μm, thus obtaining an aramid diaphragm for lithium batteries.
[0041] Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the aramid polymer solution in the aramid slurry raw material comes from Preparation Example 5.
[0042] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that no Tencel fibrillated slurry is used in the aramid slurry raw material.
[0043] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that lithium aluminum titanium phosphate nanoparticles are not used in the aramid slurry raw material.
[0044] Performance testing The following performance tests were performed on the aramid diaphragms for lithium batteries provided in Examples 1-8 and Comparative Examples 1-3 of the present application. The specific test results are shown in Table 1.
[0045] Detection Methods 1. Heat shrinkage performance Thermal shrinkage test: Expel the air between the membranes of the aramid diaphragm sample for lithium battery prepared in this application, cut it into a size of 300*100, measure the length A1 and width B1 of the cut sample, place the sample in an oven at 140°C for 2 hours, take out the diaphragm and cool it for 10 minutes, then measure the length A2 and width B2 of the sample; the thermal shrinkage performance of the diaphragm is characterized by the longitudinal thermal shrinkage rate and transverse thermal shrinkage rate of the diaphragm, the longitudinal thermal shrinkage rate of the diaphragm = ((A1-A2) / A1)x100%; the transverse thermal shrinkage rate of the diaphragm = ((B1-B2) / B1)x100%.
[0046] 2. Air permeability The air permeability of the aramid diaphragm for lithium battery prepared in the present application was tested using an air permeability tester.
[0047] 3. Porosity The test was conducted by the n-butanol absorption method: a circular aramid diaphragm with a diameter of 18 mm prepared in the present application was immersed in n-butanol solution for 4 h, the mass after immersion was weighed, and the porosity was calculated by the formula = [(M1-M0) / ρV]×100, where M0 and M1 are the masses of the diaphragm before and after immersion in n-butanol, respectively, in g; ρ is the density of n-butanol, 0.81 g / cm 3 ; V is the volume of the aramid diaphragm, in cm 3 .
[0048] Table 1: Performance test results data table It can be seen from the performance test results that the aramid diaphragm for lithium batteries prepared in this application has good thermal stability, reduces the phenomenon of thermal shrinkage of the diaphragm at high temperatures, and can also maintain good porosity and air permeability, thereby improving the electrochemical stability of the lithium battery. By comparing Example 8 with Example 1, it can be seen that by silanizing the nano-ceramic particles using a silane coupling agent, it can be seen from the performance test results that the air permeability and thermal stability of the prepared aramid diaphragm are significantly improved, further illustrating that the nano-ceramic particles are modified by a silane coupling agent, the precipitation of the nano-ceramic particles is reduced, and the bonding force between the aramid slurry and the base film is enhanced, thereby improving the thermal stability and strength of the aramid diaphragm.
[0049] By comparing Comparative Examples 1-3 with Example 1, it can be seen that the aramid polymerization liquid in Comparative Example 1 does not use polyether surfactant, the aramid slurry raw material in Comparative Example 2 does not use Tencel fibrillated slurry, and the aramid slurry raw material in Comparative Example 3 does not use lithium titanium aluminum phosphate nanoparticles. It can be seen from the performance test results that the porosity and thermal stability of the prepared aramid diaphragm are reduced, which in turn affects the electrochemical properties of the lithium battery.
[0050] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. An aramid diaphragm for a lithium battery, characterized in that: The invention comprises aramid slurry and a base film, wherein the aramid slurry is coated on both sides of the base film to form an aramid coating, wherein the aramid slurry comprises the following raw materials in parts by weight: 20-40 parts of aramid polymer solution, 5-10 parts of tencel fibrillated slurry, 1-3 parts of lithium titanium aluminum phosphate nanoparticles, 3-5 parts of nano ceramic particles, and 8-15 parts of solvent; the aramid polymer solution comprises the following raw materials in parts by weight: 1-3 parts of p-phenylenediamine, 60-80 parts of polar solvent, 5-10 parts of terephthaloyl chloride, 1-3 parts of 3,4'-diaminodiphenyl ether, 1-3 parts of o-chloro-p-phenylenediamine, and 0.5-1 part of a polyether surfactant.
2. The aramid separator for lithium battery according to claim 1, characterized in that: The polyether surfactant is one of polyethylene glycol, polypropylene oxide and polytetramethylene glycol.
3. The aramid separator for lithium battery according to claim 1, characterized in that: The solvent is a complex of a dispersing solvent and a co-solvent, the dispersing solvent is at least one of dimethylacetamide, dimethylformamide, dimethyl sulfoxide, and acetone, and the co-solvent is at least one of calcium chloride, lithium chloride, and potassium hydroxide.
4. The aramid separator for lithium battery according to claim 1, characterized in that: The Tencel fibrillated pulp is prepared by subjecting Tencel fibers as raw materials to pulping and fibrillation treatment, and the Tencel fibrillated pulp has a beating degree of 75-85° SR.
5. The aramid separator for lithium battery according to claim 1, characterized in that: The nano ceramic particles are silanized and modified using a silane coupling agent. The modification method comprises the following specific steps: mixing the nano ceramic particles with the silane coupling agent and toluene, heating to 70-80° C. and stirring evenly, washing and drying to obtain silanized modified nano ceramic particles.
6. The aramid separator for lithium battery according to claim 5, characterized in that: The nano ceramic particles are at least one of nano silicon dioxide, nano titanium dioxide and nano aluminum oxide.
7. The aramid separator for lithium battery according to claim 1, characterized in that: The thickness of the aramid coating is 3-8 μm, and the thickness of the base film is 5-20 μm.
8. A method for preparing an aramid diaphragm for a lithium battery according to any one of claims 1 to 7, characterized in that: The specific steps include: The p-phenylenediamine, 3,4'-diaminodiphenyl and o-chloro-p-phenylenediamine are uniformly mixed, a polar solvent is added, and the mixture is stirred and dissolved at 10-30°C under the protection of nitrogen, and then the mixture is cooled to -5°C-0°C, terephthaloyl chloride and a polyether surfactant are added, and the mixture is stirred and reacted to obtain a reaction mixture, and the pH of the reaction mixture is adjusted to obtain an aramid polymerization solution; Aramid polymer solution, Tencel fibrillated pulp, lithium titanium aluminum phosphate nanoparticles, nano-ceramic particles and solvent are mixed, stirred and dissolved to obtain aramid slurry, and then the aramid slurry is coated on both sides of the base film and dried to form an aramid coating to obtain an aramid diaphragm for lithium batteries.
Citation Information
Patent Citations
Lithium ion battery separation membrane substrate, preparation method and applications thereof
CN108598337A
P-aramid coating slurry, preparation method for p-aramid coating slurry, p-aramid diaphragm, preparation method for p-aramid diaphragm and secondary battery
CN109411676A
Inorganic nanoparticle-modified aramid fiber paste and aramid-coated lithium battery composite diagram
CN110048063A
P-aramid fiber and preparation method thereof
CN110499542A
Lithium battery diaphragm and preparation method thereof
CN110993868A
Cited By
Para-aramid lithium battery diaphragm and preparation method thereof
CN121307432A
Solid ionic conductor aramid fiber composite diaphragm and preparation method thereof
CN121812892A